2017
DOI: 10.1016/j.canlet.2016.10.021
|View full text |Cite
|
Sign up to set email alerts
|

Prostate cancer-associated mutation in SPOP impairs its ability to target Cdc20 for poly-ubiquitination and degradation

Abstract: Recent studies revealed that mutations in SPOP (Speckle-type POZ protein) occur in up to 15% of patients with prostate cancer. However, the physiological role of SPOP in regulating prostate tumorigenesis remains elusive. Here, we identified the Cdc20 oncoprotein as a novel ubiquitin substrate of SPOP. As such, pharmacological inhibition of Cullin-based E3 ligases by MLN4924 could stabilize endogenous Cdc20 in cells. Furthermore, we found that Cullin 3, and, to a less extent, Cullin 1, specifically interacted w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 39 publications
(33 citation statements)
references
References 48 publications
0
33
0
Order By: Relevance
“…Recently, Sackton et al (26) reported that apcin directly disturbed the binding of Cdc20 to its substrates and subsequently blocked mitotic exit in human cancer cells. Apcin inhibited the oncogenic function of Cdc20 by reducing cell viability and inducing apoptosis in a dose-dependent manner in prostate cancer cells (39). Furthermore, it was reported that Speckle-type POZ protein (SPOP)-deficient prostate cancer cells were resistant to apcin, suggesting that apcin could be clinically used to treat patients with SPOP-WT prostate cancer, but not SPOP-deficient prostate cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Sackton et al (26) reported that apcin directly disturbed the binding of Cdc20 to its substrates and subsequently blocked mitotic exit in human cancer cells. Apcin inhibited the oncogenic function of Cdc20 by reducing cell viability and inducing apoptosis in a dose-dependent manner in prostate cancer cells (39). Furthermore, it was reported that Speckle-type POZ protein (SPOP)-deficient prostate cancer cells were resistant to apcin, suggesting that apcin could be clinically used to treat patients with SPOP-WT prostate cancer, but not SPOP-deficient prostate cancer.…”
Section: Discussionmentioning
confidence: 99%
“…The CRL3 E3 ligase containing SPOP acts as a tumor suppressor by promoting the degradation of several oncogenes, including ERG and CDC20 (296), an activator of the APC/C E3 ligase. Consequently, mutations that inactivate SPOP function are present in 15% of prostate cancers (193).…”
Section: Tumorigenesis: Somewhere Between Neutrality and Lethalitymentioning
confidence: 99%
“…SPOP suppresses tumorigenesis and progression via regulation of cell growth, apoptosis, migration, invasion and drug resistance by targeting its downstream substrates in several types of human malignancies, including prostate, lung, gastric, liver, colon and endometrial cancers SPOP mutations and downregulation were detected in human PrCa tissues, and these mutations were also tightly correlated with a worse prognosis in patients with PrCa [61]. More importantly, extensive biochemical evidence has further indicated that SPOP functions as a tumor suppressor by promoting the degradation of oncogenic substrates in PrCa, including SRC3 [62], AR [63], TRIM24 [64], c-Myc [65], DEK [66], SENP7 [67], EglN2 [68], ATF2 [69], Cdc20 [70], ERG [71,81], BRD4 [72][73][74], PD-L1 [75] and cyclin E1 [76]. Due to the many publications and space limitations, we will not describe the tumor suppressive role that SPOP plays by promoting the ubiquitination and degradation of its substrates in PrCa in detail.…”
Section: Prostate Cancer (Prca)mentioning
confidence: 99%